Social Recognition on a Global Scale: Opportunities and Limits of Media Reflection - Solík, Martin; Mináriková, Juliána (Communication Today, 2025)
The study deals with the issues of social recognition in global space, focusing on its media reflection. Even though recognition is one of the key terms discussed by contemporary Philosophy – and by Social Sciences as a whole – it tends to be reflected and formulated mostly on interpersonal or local levels. The authors put special emphasis on the problem of solidarity in the context of recognition, pointing out that solidarity, as a form of recognition, is not associated with any adequate parallels behind the borders of national states – this fact is obvious mostly in transnational economy. Taking into account this basic assumption, the study aims to articulate extraterritorial recognition of the possessors of social rights on international and transnational levels of justice. It is obvious that people living in countries of the ‘Third World’ are not able to express their disagreement through ways and means typical for the Western civilization. Their fights for recognition also represent fighting for water, food, shelter, etc. The authors therefore point out the problem related to thematic agenda of the media, which demonstrates the possibilities and limits of media reflection – they have to select between large amounts of different events and news, and thus pay attention only to a limited number of information, missing out the problems associated with absent solidarity on a global scale. In addition, opportunities and limits of media communication linked to articulation of the global fights for social recognition cannot be omitted, especially in the context of following argumentation of possible scenarios that focus on re-formulation of public interests. The authors claim that national states should use their influence in global and transnational organizations, and media need to trengthen their information function in order to offer relevant information about important events related to the ‘Third World’ countries. However, economic interests of transnational corporations seem to be one of the limits of this process. Even though we are able to witness the dynamic development progress of alternative information sources, their credibility has not been able to match the level of influence of global information networks yet.